The application of the metaverse in surgical clinical teaching: transforming medical education through immersive approaches - Yu, Tao; Yang, Zhichao; Zhang, Meng; Yao, Lin; Sun, Xiaodan (Frontiers in Oncology, 2025)
With the rapid development of immersive technologies such as virtual reality (VR) and augmented reality (AR), the Metaverse is emerging as a transformative platform in medical education. This study examines the integration of the Metaverse into surgical clinical teaching, highlighting its potential to enhance educational outcomes, overcome traditional limitations, and foster global collaboration in medical training. Core features of the Metaverse offer medical students a safe virtual setting for practicing complex surgical procedures and honing clinical decision-making skills. However, significant challenges remain, including high technological costs, substantial equipment requirements, and the complexity of content development. Ethical concerns, particularly regarding data privacy and the psychological impact of immersive experiences, also require careful consideration. This paper calls for strategic planning, interdisciplinary collaboration, and ongoing research to fully realize the transformative potential of the Metaverse in surgical clinical education, ultimately improving the quality and effectiveness of medical training.